Awareness of cardiovascular disease risk and care received among Australian women with a history of hypertensive disorders of pregnancy: a cross-sectional survey - Kaylee Slater; Rachael Taylor; Clare E. Collins; Melinda Hutchesson (BMC Pregnancy and Childbirth)
Abstract Background Women with a history of hypertensive disorders of pregnancy (HDP), including chronic hypertension, gestational hypertension, and preeclampsia have an increased risk of cardiovascular disease (CVD). Current research suggests that general practitioners are unaware of women’s HDP history, and although ideally placed to follow-up with these women, there is limited understanding of current CVD prevention practices in women after HDP. Additionally, preeclampsia confers a higher CVD risk compared to other types of HDP, and Australian research suggests that lower socioeconomic status (SES) is associated with a higher incidence of both HDP and CVD. Therefore, the aim of the analysis was to investigate awareness of CVD risk and care received from health professionals among women with a history of HDP and examine differences between type of HDP and SES. Methods Analysis of a cross-sectional survey of 293 Australian women with a history of HDP (from 2017 onwards). Data were analysed using basic descriptive statistics. To assess differences in HDP type and SES, one-way ANOVA was used to assess continuous variables and χ2 tests for categorical variables, with P < 0.05 considered statistically significant. Results Most women with a history of HDP were unaware of their increased CVD risk (68%). Women with a history of preeclampsia, gestational hypertension or preeclampsia were more aware of CVD risk compared to those with chronic hypertension (p = 0.02). Regardless of HDP type or SES, women post-HDP were less likely to receive assessment and management of lifestyle CVD risk factors compared to blood pressure. Most women felt supported in managing stress and mental health, but not for managing body weight, smoking and sleep. Conclusions Women with a history of HDP are unaware of their increased CVD risk and are not receiving recommended CVD preventative care, irrespective of HDP type and/or SES. Findings should be used to inform development of tailored CVD prevention interventions in the primary care setting for women following HDP.